Development and prototyping an automatic fish feeder - Mohd Nizam, Mohd Nor (2008)
An automatic device to feed fish at predetermined amounts of food and time. Fish feeder combines mechanical and electrical system to control fish feeding activity. This device consists of pellet tank, distributor and a stand. The dispensed food will be controlled by a motor which situated under the tank. A propeller design that differs by angle of force applied to spread the food, will distribute the pellet onto wider water surface which is controlled by the outlet gap. A control system attached to this device allows the fish to be fed at predetermined food amount and time. Timer is used to control the motor which run the gear and propeller to increase functional efficiency. The fish feeder is successfully fabricated and tested. Feeding can be done at predetermined interval of time and accurate amount of food with larger surface area covered by pellet is obtained. Furthermore the waste of fish food in pond is reduced efficiently.